Charity Law, The Advancement of Religion and Public Benefit – Will the United Kingdom Be The Answer to New Zealand’s Prayers? - Chevalier-Watts, Juliet (Victoria University of Wellington Law Review, 2016)
The law of charity and religion has an ancient relationship and religion, for charity law purposes, recognises a plethora of belief systems. However, for a religion to be recognised at law in New Zealand and in the United Kingdom it must have public benefit, whether that is a presumed requirement or to be shown expressly. This requirement of public benefit has generated much debate over the decades, in parliaments, in courts and in academia. This article considers the very real issues associate with public benefit and the advancement of religion in charity law and asks whether the contemporary approach of the United Kingdom with regard to the removal of the presumption of public benefit would provide a more certain legal path for New Zealand courts and charitable bodies.